Ties that bind: Young people, community and social capital in the wake of the pandemic - Rhiannon Barker; Sophie Rowland; Claire Thompson; Karen Lock; Katie Hunter; Jin Lim; Dalya Marks (Elsevier, 2022)
The connection that young people have to their local neighbourhood and community has been shown to impact on health and wellbeing, particularly for those living in the most deprived areas. We report on a qualitative participatory study using photo elicitation methods undertaken in three deprived neighbourhoods across London exploring concepts of community and social connection, with young people aged 13-24 years, against the backdrop of the COVID-19 pandemic. The construct of social capital, referring to the extent of solidarity and connection between groups, has been shown to impact on pandemic related outcomes, and is used in this study as a lens to enhance understanding of young people's experience of the pandemic.Young people created heterogenous physical social ties across class, ethnicity, and geographical area which were important during the pandemic, although these may be jeopardised by a range of factors including fear of violence, mistrust of those in power, parental control and place-based inequity. The isolation and localism enforced by the pandemic encouraged young people to pay more attention to the value of local connections they built up both with people and place.Place-based research needs to continue a dialogue with young people, acknowledging and drawing on existing networks, community assets and cultural beliefs. The impact of COVID-19 on accentuating existing inequalities means that the need for place-based action, addressing the social determinants of health and involving the experiences and input of the young, is more vital than ever.